Pendidikan Generasi Penerus Muhammadiyah: Mengintegrasikan Nilai-nilai Islam dan Keterampilan Modern untuk Mewujudkan Generasi Berkemajuan - Mada Yudha Sasana; Bagus Jamroji; Lilik Noer Laili; Muhammad Al Haariz (Educational Research Center, 2026)
This study examines the integration of Islamic values and practical skills in Muhammadiyah education as an effort to create a competent and character-driven generation in the era of globalization. Muhammadiyah education, rooted in the thoughts of KH. Ahmad Dahlan, promotes the concept of integration between religious and worldly knowledge, aiming to produce individuals who are not only academically intelligent but also possess high morals. This study uses a qualitative library approach with a literature analysis method to explore and analyze how Muhammadiyah developed a curriculum that combines these two aspects. The findings indicate that this integration is crucial for producing graduates who are ready to face global challenges, by balancing religious knowledge and practical skills relevant to the needs of the times. Furthermore, this study emphasizes the importance of a holistic approach in education, which focuses not only on cognitive aspects but also on character development and social skills. Thus, Muhammadiyah education has the potential to become a model in creating a young generation ready to compete globally while adhering to strong religious values.